2010
DOI: 10.3945/ajcn.2009.29007
|View full text |Cite
|
Sign up to set email alerts
|

Hedonic hunger is increased in severely obese patients and is reduced after gastric bypass surgery

Abstract: In comparison with nonobese control subjects, severely obese patients display a marked increase in hedonic hunger that is not observed in patients who have undergone gastric bypass surgery, suggesting that the operation normalizes excessive appetite for palatable foods, which may be an important pathophysiologic feature of severe obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
110
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 35 publications
10
110
2
1
Order By: Relevance
“…Our finding of higher PFS aggregated, subscale ‘food available’ and ‘food present’ scores in the obese type 2 diabetes patients when compared with the non‐obese counterparts is in keeping with the previous reports of a positive relationship between BMI and PFS scores in severely obese individuals who received bariatric‐surgery11 or attended a clinical weight‐loss treatment program12. This observation suggests that hedonic eating drives are significantly increased in these severe obese patients, and might be an important driver in the pathogenesis of obesity and its related diseases.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding of higher PFS aggregated, subscale ‘food available’ and ‘food present’ scores in the obese type 2 diabetes patients when compared with the non‐obese counterparts is in keeping with the previous reports of a positive relationship between BMI and PFS scores in severely obese individuals who received bariatric‐surgery11 or attended a clinical weight‐loss treatment program12. This observation suggests that hedonic eating drives are significantly increased in these severe obese patients, and might be an important driver in the pathogenesis of obesity and its related diseases.…”
Section: Discussionsupporting
confidence: 92%
“…Hedonic hunger, a relatively new construct, refers to the appetitive drive to eat palatable foods, particularly those high in fat and/or sugar, in the absence of a physiological need (i.e., caloric deficit) in an obesogenic food environment9. Previous studies reported that obese adults expressed higher hedonic hunger than non‐obese controls10, 11. Furthermore, interventions, such as weight loss programs and bariatric surgeries, have shown the impact of these treatment strategies on the change in levels of hedonic hunger in obese individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Elevated PFS scores have been associated to both obesity 17,18 and binge eating. 19,20 Furthermore, fasting periods equivalent to regular breaks between meals (e.g., 4 hours) are not associated with changes in scores on the PFS, suggesting that hedonic hunger is a stable construct that is not considerably affected by daily variations in physical or homeostatic hunger.…”
mentioning
confidence: 99%
“…However, in morbidly obese patients from a bariatric surgery clinic, DEBQ external eating subscale scores were significantly reduced after weight-loss surgery, 35 and similar findings have been reported regarding reduction of PFS scores after weight-loss surgery. 17,36 Longitudinal studies are thus needed to clarify if PFS and DEBQ subscales, namely the external eating subscale, can serve as predictors of weight gain, presumably acting as markers of hedonically mediated overeating.…”
mentioning
confidence: 99%